Quantum chemical study of the spatial and electronic structure of the active centers of the defect-free nano-dispersed anatase surface and it’s derivative doped with Ag2 cluster - Filonenko О.V.; Lobanov, V.V.; Yavorovsky, O.P.; Riabovol, V.M.; Zahornyi М.М.; Khyzhun О.Y. (Physics and Chemistry of Solid State, 2025)
The density functional method with a hybrid exchange-correlation B3LYP functional and the valence basis set sbkjc with an effective core potential was used to perform quantum chemical modeling of Ag dimers' adsorption centers on the anatase surface. Changes in the geometric and electronic structure of the Ag2 cluster during adsorption were analyzed, and the most stable positions on the TiO2 surface were determined.